The dirichlet problem for a class of anisotropic Schrödinger-Kirchhoff-type equations with critical exponent - Chems Eddine, Nabil; Nguyen, Anh Tuan; Ragusa, Maria Alessandra (Mathematical Modelling and Analysis, 2024)
In this paper, our focus lies in addressing the Dirichlet problem associated with a specific class of critical anisotropic elliptic equations of Schrödinger-Kirchhoff type. These equations incorporate variable exponents and a real positive parameter. Our objective is to establish the existence of at least one solution to this problem.